Pelestarian Sembahyang Ceng Beng di Indonesia - Wenly, Evina (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
Cengbeng Prayer is a tradition of praying to ancestral graves that has been carried out since the Jin dynasty (265-420 AD). On the day of the Cengbeng prayer, which has become a tradition, families of Chinese descent go to the graves of their parents or ancestors to clean and pray there. Especially in Singkawang, the Cengbeng prayer is performed twice a year, namely the second month and seventh month of the lunar calendar （阴历）. This study aims to find out the reasons for the preservation of the thousand-year- old Cengbeng prayer, what thoughts are behind it. The method used is interviews with people who perform the Cengbeng prayer. Data were obtained from answers to questions given during interviews. The data was analyzed using the teachings of Confucius 孝 and 家 to get an idea about the preservation of this Cengbeng prayer. Data is presented descriptively and qualitatively with simple quantitative calculations through graphs. There were eight informants, still under 40 years old. This research is field research that uses the philosophical teachings of Confucianism in its analysis. The results of the analysis show that the teachings of Confucius